The prehistory of Britain and Ireland - Bradley, Richard (Cambridge University, 2013)
In this study Richard Bradley offers a new interpretation of the unique archaeological record of these islands based on a wealth of current and largely unpublished data. He surveys the entire archaeological sequence over a 4000 year period, from the adoption of agriculture in the Neolithic period to the discovery of Britain & Ireland.